Age-associated and Breed-associated Variations in Haematological and Biochemical Variables in Mangalitsa, Mangalitsa×Durock and Large White Pig - Stevančević, Ognjen; Cincović, Marko; Šević, Radosav; Savić, Božidar; Belić, Branislava; Stojanac, Nenad; Lakić, Ivana; Kovačević, Zorana (Acta Scientiae Veterinariae, 2019)
Background: Research of hematologic and biochemical parameters in pigs is of great importance considering the fact that pigs are used as a model in research of different health disorders in humans. There are many different breeds of pigs that have different health, productive and biologic characteristics that need to be studied. Hematologic and biochemical values can vary dependent on presence of inflammation and infection.The aim of this study was to determine the influence of breed, age and their interactions on hematologic and biochemical parameters on blood of mangalitsa, mangalitsa x durock and Large White pig. Materials, Methods & Results: Experiment included 10 litters of mangalitsa, white variety, mated with mangalitsa boar, 10 mangalitsa litters, and white variety inseminated with durock boar and litters of great Large White inseminated with great Yorkshire boar. Six groups, each include 10 animals were formed and their blood was sampled (3 breeds and 2 age categories). Age groups were formed according to moment of blood sampling. First sample was taken in moment of 30 ± 5 kg of body weight. Second sample was taken when body weight was 100 kg hematologic analyze. Samples were taken with BD Vacutainer®. Complete classic blood analyzes and leucocytes formulas were done by hematology analyzer ADVIA 120 Hematology Siemens, Germany. Biochemical analyze was done by biochemical analyzer A15 BioSystem with their standard colorimetric reagenses. Concentration of total protein, albumin, urea, creatinine, cholesterol, total bilirubin, AST and ALT were determined. Globulin concentration was calculated. Results have showed that hematologic and biochemical parameters are influenced by breed, age and their interaction as: total leukocyte number (age, breed x age), neutrophils number (age, breed), number of monocytes and platelets (age, breed x age), eosinophils number and percentage (age), percentage of neutrophils, percentage of lymphocytes and cholesterol (breed). All of three factors (breed, age breed x age) have affected number of lymphocytes basophils number, % of monocytes, % of basophils, erythrocyte number, hemoglobin concentration, hematocrit, MCV, MCH, MCHC, RDW, protein, albumin, creatinine and ALT. Globulin value varied in function of interaction breed x age. RBC, Hgb, Hct, MCV, MCH, MCHC, total protein albumin, creatinine, and ALT variance can be explained by influence of breed, age and their interaction (η2 = 35-75%). Discussion: Based on results of this study breed and age have significant influence on numerous blood parameters. Besides the differences in mean values of parameters it is proved presence of statistically significant difference in frequencies distributions in function of age and breed. Different age and breed categories have different frequencies distributions of many determined parameters. There is positive correlation between RBC, Hgb, Hct and albumin in all three breed (R2 = 67-84%). Negative correlation was found between WBC and RBC, Hgb, Hct that was statistically significant in mangalitsa breed (R2 = 58-69%) but not in other two breeds. In mangalitsa significant positive correlation was found between globulin and leukocyte number. Given values have showed that during interpretation of lab results breed, age and interactions of hematologic and biochemical parameters need to be considered. Mean values and frequencies distribution differences lead to redefinition of referent range in function of breed and age that requires further research.